2018
DOI: 10.4174/astr.2018.94.5.279
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal anti-inflammatory drugs induced diaphragm disease: a report of 3 cases and literature review

Abstract: Multiple strictures of small bowel induced by nonsteroidal anti-inflammatory drugs (NSAIDs), were known as diaphragm disease. The purpose of these case reports is to present 3 cases of diaphragm disease of small bowel and summarize the clinical features of this disease entity. A 34-year-old man, a 63-year-old man, and a 66-year-old woman were admitted to Daegu Catholic University Medical Center because of recurrent intestinal obstructions. Two of these patients had taken heavy NSAIDs use. Capsule endoscopy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…She was diagnosed with capsule endoscopy and managed by strict plastic surgery [ 11 ]. Another report of three cases who were diagnosed with NSAID-induced diaphragm disease showed that the capsule endoscopy showed circumferential strictures of the ileum, which were managed by segmental resection and enterotomy [ 12 ]. Another case of a 60-year-old Irish male was diagnosed with multiple intestinal diaphragms unmasked with severe duodenal ulcers that resulted from long-term exposure to 5-aminosalicylic acid (5-ASA) and immune suppression and was investigated by abdominal endoscopy and CT scanning [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…She was diagnosed with capsule endoscopy and managed by strict plastic surgery [ 11 ]. Another report of three cases who were diagnosed with NSAID-induced diaphragm disease showed that the capsule endoscopy showed circumferential strictures of the ileum, which were managed by segmental resection and enterotomy [ 12 ]. Another case of a 60-year-old Irish male was diagnosed with multiple intestinal diaphragms unmasked with severe duodenal ulcers that resulted from long-term exposure to 5-aminosalicylic acid (5-ASA) and immune suppression and was investigated by abdominal endoscopy and CT scanning [ 13 ].…”
Section: Discussionmentioning
confidence: 99%